Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
Your solution is (3/2, -7/2)
Step-by-step explanation:
y = x - 5
y = -3x + 1
First, see that these two equations equal y. This means you can set them equal to each other.
x - 5 = -3x + 1
Combine like terms.
[add 3x to both sides]
4x -5 = 1
[add 5 to both sides]
4x = 6
Isolate x further by dividing both sides by 4.
x = 6/4
Simplify the fraction.
x = 3/2
Now that we know x, plug its value (3/2) back into one of the original equations to find y.
y = (3/2) - 5
Simplify by subtracting.
[convert 5 to have a denominator of 2]
y = 3/2 - 10/2
y = -7/2
Your solution is (3/2, -7/2)
Check this by plugging these values into the equation you have not yet checked.
-7/2 = -3(3/2) + 1
Simplify.
[multiply]
-7/2 = -9/2 + 1
[convert 1 to have a denominator of 2]
-7/2 = -9/2 + 2/2
[add]
-7/2 = -7/2
This equation is true; therefore your solution is correct.
Hope this helps!
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.